EFFECT OF CENTRAL OBESITY AS RISK FACTOR OF METABOLIC SYNDROME - Djausal, Anisa Nuraisa (Majority, 2015)
Abstract Metabolic syndrome is not a disease, its an association of risk factor of metabolic abnormalities involves with visceral obesity, high levels of triglyverides and glucose, low level of High Density Lipoprotein (HDL) and hypertension which can increase the risk of type-2 diabetes mellitus and cardiovascular disease. The risk factors of metabolic syndrome are genetic, central obesity, lack of physical activity and age. Obesity is an abnormalities condition or accumulation of excess fat in adipose tissues, caused from increased size and number of adipose tissue which can lead to metabolic abnormality. Central obesity is one of the most significant factor that affect the insulin resistance. Some factors that can affect the insulin resistance are lipotoxicity, adipocytokines, adinopectine, leptin, interleukin-6, resistin, and TNF-α. There is two kind of obesity, central obesity and peripheral obesity. Central obesity is one of risk factors of metabolic syndrome. Visceral obesity or central obesity are more dangerous because the lipolysis in this area are very efficient and more resistant to insulin effect than other adipocite area. Keywords: central obesity, metabolic syndrome, obesity, risk factor. Abstrak Sindrom metabolik bukanlah suatu penyakit, tetapi merupakan sekumpulan faktor risiko kelainan metabolisme, yang ditandai dengan obesitas viseral, meningkatnya kadar trigliserida dan glukosa, rendahnya kadar High Density Lipoprotein (HDL) dan hipertensi yang dapat menyebabkan peningkatan risiko terjadinya diabetes mellitus tipe-2 dan penyakit kardiovaskuler. Faktor resiko sindrom metabolik adalah genetik, obesitas sentral, kurangnya aktivitas fisik dan usia. Obesitas merupakan kondisi ketidaknormalan atau kelebihan akumulasi lemak dalam jaringan adiposa, karena bertambahnya ukuran dan jumlah sel jaringan adipose yang dapat menyebabkan gangguan metabolisme. Obesitas sentral merupakan faktor yang sangat berpengaruh dalam mencetuskan terjadinya resistensi insulin. Hal-hal yang dapat menyebabkan terjadinya resistensi insulin, antara lain lipotoksisitas, adipositokin, adinopektin, leptin, interleukin-6, resistin dan TNF-α. Terdapat dua tipe obesitas yaitu obesitas sentral dan perifer. Obesitas sentral merupakan salah satu faktor resiko sindrom metabolik. Obesitas viseral atau obesitas sentral lebih berbahaya karena lipolisis di daerah ini sangat efisien dan lebih resisten terhadap efek insulin dibandingkan dengan adiposit didaerah lain. Kata kunci: faktor resiko, obesitas, obesitas sentral, sindrom metabolik.